(untitled) (Global Journal of Management and Business Research, 2015)
The education is considered as the backbone of any country In Punjab the number of total number of primary schools is 18045 Total 139317990 students have been enrolled in these schools for the primary education In Punjab the number of these students is 2349111 The total number of teachers enrolled in the secondary education is 1063420 in India whether in Punjab this number is 138939 Source selected educational statistics 2008 MHRD The employee satisfaction is an important aspect to run any of the organization The case is same in the education industry as well The quality of the student depend on the quality of teaching and teachers which is directly linked to the satisfaction The current study attempt to study the satisfaction of the government schools teachers in Ludhiana Punjab